(untitled) (Conferencea, 2024)
Pollution of rivers is an important environmental and microbiological problem. As a result of anthropogenic impact, various biogenic or toxic compounds flowing into water bodies disturb the balance in the ecosystem, as a result of which its self-cleaning process decreases. Water pollution is often considered to be the cause of many diseases and increasing mortality. Various waterborne infectious diseases may be caused by pathogenic microorganisms. To assess the ecological safety of rivers, it is necessary to carry out their microbiological analysis. The object of our research was the Khrami River basin of Eastern Georgia. Monitoring was conducted in October 2023. We conducted observations at two points: river Khrami No.1 and river Khrami No.2 (river Khrami and the Mashavera after joining). Total coliform bacteria, E.coli, mesophilic aerobes, facultative anaerobes, coliphages, salmonella, and Streptococcus faecalis were determined to determine the sanitary-microbiological condition of the Khrami river water. Based on the results of the analysis, Salmonella was not detected in any of the river water samples, and the other microbiological indicators exceeded the values allowed by the surface water norms.